2019
DOI: 10.1111/vco.12528
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of weight loss in canine cancer bearing patients undergoing radiation therapy

Abstract: Critical weight loss, as defined by ≥5% decrease in body weight, has been associated with increased morbidity and mortality in human patients with cancers of the head and neck. Weight loss has anecdotally been reported to occur frequently in veterinary patients undergoing radiation therapy and is hypothesized to be more severe in patients with cancers of the head and neck, along with those hospitalized during radiation therapy. The primary objective of this retrospective study was to evaluate the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Weight loss in the EBRT group intensified from the 16th day after treatment, although the animals lost less weight than the control group. Radiotherapy has previously been shown to be associated with side effects such as loss of appetite, fatigue and, diarrhoea that can lead to weight loss [ 17 , 46 ]. In clinical studies, it has been observed that weight loss due to radiotherapy can continue for up to 1 month after treatment, which could explain the continuation of the weight loss in our study [ 17 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss in the EBRT group intensified from the 16th day after treatment, although the animals lost less weight than the control group. Radiotherapy has previously been shown to be associated with side effects such as loss of appetite, fatigue and, diarrhoea that can lead to weight loss [ 17 , 46 ]. In clinical studies, it has been observed that weight loss due to radiotherapy can continue for up to 1 month after treatment, which could explain the continuation of the weight loss in our study [ 17 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…(c) Changes in body contour were not considered. Marked weight loss during radiation therapy associated with possible body contour changes was rare according to a recent study 39 . However, body contour changes are still possible despite stable weight and can for example happen in the region of movable skin folds in the inguinal and/or abdomen region according to personal experience.…”
Section: Discussionmentioning
confidence: 99%